Investigating handgrip strength and flexibility as independent fitness indicators among Malaysian university students / Mohamad Fardeen Aqasha Mohamad Shah ... [et al.]. - Mohamad Shah, Mohamad Fardeen Aqasha; Aziz, Iqbal Husaini; Syafiq, Wan Mohd; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Haziq, Amrun; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Handgrip strength and flexibility are vital components of physical fitness, often linked to overall health and athletic performance. Despite their importance, the relationship between these measures remains underexplored, especially in young adults. This study examines handgrip strength, flexibility, and correlation among university students, aiming to enhance the understanding of fitness assessments and inform strategies for promoting health in this demographic [1]. Handgrip strength was measured using a digital hand dynamometer, with participants using their dominant hand to record the highest value from three attempts [2]. Flexibility was assessed using the sit-and-reach test, with participants reaching forward three times, and the best distance recorded [3]. The study included 23 university students aged 18–25 from UiTM Seremban 3, selected based on specific eligibility criteria and informed consent.